PENGARUH PELAYANAN FISKUS, EFEKTIVITAS SISTEM PERPAJAKAN, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DI KPP PRATAMA BATAM SELATAN - Pasaribu, Sara; Husda, Anggun Permata (LPPM Universitas Putera Batam, 2023)
Taxpayer compliance is a situation where the taxpayer fulfills all tax obligations and exercises his tax rights. This study aims to determine and analyze the influence of tax authorities, effectiveness of the tax system, and awareness of taxpayers on taxpayer compliance. Researchers used quantitative research with a sample of 100 people obtained using the formulaslovin. The sampling technique used in this study isprobability by methodsimple random sampling. Data collection was carried out by distributing questionnaires and using a Likert scale which was then processed using the SPSS Version 25 program. The results showed that the tax service variable had an effect on individual taxpayer compliance with a significant T-test value of 0.001 which is less than 0.05. The effectiveness of the taxation system variable also influences individual taxpayer compliance with a significant T-test value of 0.001 which is less than 0.05. As well as the variable taxpayer awareness has an effect on individual taxpayer compliance with a significant value of the T test of 0.006 which is less than 0.05. This gives the conclusion that the variables of tax authorities, the effectiveness of the taxation system, and taxpayer awareness have an effect on taxpayer compliance